1974
DOI: 10.1113/jphysiol.1974.sp010719
|View full text |Cite
|
Sign up to set email alerts
|

Fall in blood pressure produced from discrete regions of the ventral surface of the medulla by glycine and lesions

Abstract: SUMMARY1. In cats anaesthetized with pentobarbitone sodium, atropinized by i.v. atropine methyl nitrate and artificially ventilated, experiments were carried out (a) to localize the site where glycine acts on the ventral surface of the medulla when, on topical application through paired Perspex rings caudal to the trapezoid bodies, it produces a fall in arterial blood pressure, (b) to compare the effects of uni-and bilateral application, and (c) to study the blood pressure effects produced by electrolytic lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
3

Year Published

1975
1975
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(122 citation statements)
references
References 17 publications
2
117
0
3
Order By: Relevance
“…But applied to region A, they caused no such inhibition; in each of the five experiments the carotid occlusion carried out during this application produced strong release of vasopressin. (Guertzenstein, 1973;Guertzenstein & Silver, 1974). In the present experiments both amino acids were found not only to lower arterial blood pressure when applied to region A, but also greatly to attenuate the pressor response to carotid occlusion when applied in high concentrations (GABA 50 and 100 mg/ml; glycine 25 and 50 mg/ml).…”
Section: Introductionmentioning
confidence: 60%
“…But applied to region A, they caused no such inhibition; in each of the five experiments the carotid occlusion carried out during this application produced strong release of vasopressin. (Guertzenstein, 1973;Guertzenstein & Silver, 1974). In the present experiments both amino acids were found not only to lower arterial blood pressure when applied to region A, but also greatly to attenuate the pressor response to carotid occlusion when applied in high concentrations (GABA 50 and 100 mg/ml; glycine 25 and 50 mg/ml).…”
Section: Introductionmentioning
confidence: 60%
“…Recently, it has been shown that a number of drugs which, on intraventricular injection affect blood pressure, heart rate, respiration or blood glucose, act in this way (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Feldberg & Gupta, 1974;Guertzenstein & Silver, 1974;Dey, Feldberg & Wendlandt, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the RVLM for maintaining blood pressure in anesthetized animals had first been documented 130 years ago [21]. However, only after the pioneer studies performed by Guertzenstein and colleagues [22] suggesting that supraspinal sympathetic vasomotor drive originates from the RVLM that truly brought researcher's attention to this brainstem area [22,23].…”
Section: Reactive Oxygen Species In the Rostral Ventrolateral Medullamentioning
confidence: 99%